Phylogenetic placement of Specklinia ordinata in Madisonia (Pleurothallidinae, Orchidaceae) - Ponert, Jan; Trávníček, Pavel; Chumová, Zuzana (Phytotaxa, 2023)
Madisonia has been delimited recently based on DNA analyses and morphological characters. In this article, we focus on Specklinia ordinata (Pleurothallidinae), a poorly known species. We obtained DNA data for this taxon and demonstrated that it is clearly a member of Madisonia. This species also shares morphological characters with Madisonia, in which we propose to include it.